Diversification of lamb meat imports in EU countries and its trends - Ochnio, Luiza; Rokicki, Tomasz; Koszela, Grzegorz; Klepacki, Bogdan (Zróżnicowanie importu mięsa jagnięcego w krajach UE i tendencje jego zmian, 2019)
The paper attempts to compare European Union countries in terms of the dynamics of changes in the value of lamb meat imports in the period 2003–2017. The standard against which this comparison was made was the average value, which should be understood as the growth dynamics of the examined feature for all EU countries together. For this purpose, tools related to the so-called Grade Data Analysis, such as the index of the unlikeness of structures “ar” (in this case a good tool to determine the direction of changes and the speed of these changes for all EU countries) and overrepresentation maps (used to visualise these changes and for their interpretation). Additionally, with the help of GDA methods, EU countries were divided into groups characterised by smaller, medium and higher dynamics of changes in lamb imports. It can be concluded that the most dynamic growth in imports of this type of meat is found among the newest EU member states. This may indicate a change in dietary preferences in these countries. It may also be related to greater accessibility to goods previously considered as luxury, greater awareness of so-called healthy foods and the improved standard of living of societies that have joined the European Union
Econometrics = Ekonometria, 2019, Vol. 23, No. 4, s. 96-111
Keywords: sheep meat imports; dynamics of growth; lamb; grade data analysis; overrepresentation maps; import mięsa owczego; dynamika wzrostu; jagnięcina; gradacyjna analiza danych; mapy nadreprezentacji